Karl Christ i Rzym nieprzemijający… - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2015)
Karl Christ belonged to the most eminent German historians of the ancient Rome of the latter half of the 20th century. He was particularly interested in the Roman Empire and its place in the European history. This was vividly reflected in his “Geschichte der römischen Kaiserzeit”, which had as many as six editions in Germany. The book conveys the conviction that the history of the Roman Empire constitutes a fundament of contemporary Europe, regardless of the assessment it received over the centuries, which was often very negative. Karl Christ believed that in our times, Roman Empire acquires a new meaning in view of the unification of Europe. Naturally enough, this engenders the question whether a similar process had taken place in the past, whether there is a model of unity and if so, whether it has a chance of being successful. It turns out that the Roman Empire, despite its weaknesses and drawbacks, can be the only point of reference, regardless of the ways in which Europe is “unified”. The observation is also applied in a broader perspective which extends beyond Europe. This is associated with the ongoing globalisation, which in its turn provokes questions about a similar phenomenon in the past, and almost automatically evokes the example of the Roman Empire. Therefore Christ decided to provide the reader with a comprehensive compendium of knowledge of the Roman Empire in a structural-dialectic approach, so as to facilitate the understanding of persistence of the ancient realm and its impact on European history, at the same time enabling one to arrive at its spiritual and cultural roots. Christ wished to acquaint the contemporary inhabitant of our continent with the dialectics of development of the Roman world, its structural evolution, internal social and cultural diffusion and finally the development of culture in all its manifestations. The historian believed that only in this fashion, i.e. not only through history of persons and events, based on sensational elements, can one appreciate the place of the Roman Empire in the developmental sequence of the European continent and its significance for the contemporary cultural shape of Europe. This is also reflected in Christ’s studies on the history of historiography, or the image of the history of ancient Rome and the specificity of the Roman Empire that had been created by various authors over the centuries. This is also where he undertook the effort to evaluate the positions assumed by German historians in the Nazi times and during the Communist era, in the German Democratic Republic. Nonetheless, the studies of history of historiography were only a means to an end, which was to promote the awareness of the importance of the Roman world, or Mediterranean civilisation as a whole, for the contemporary European culture as well as highlight its persisting influence. In Christ’s opinion, it is that “dialogue of a historian with history” which demonstrates to the fullest extent the dialectic bond between antiquity and the present day. słowa klucze